Green coal substitutes for boilers through hydrothermal carbonization of biomass: pyrolysis and combustion behavior. (15th July 2023) - Böttger, Jannik; Eckhard, Till; Pflieger, Christin; Senneca, Osvalda; Muhler, Martin; Cerciello, Francesca
Highlights: Influence of Hydrothermal Carbonization (HTC) on different biomass. HTC reduces hemicellulose and amorphous cellulose. HTC samples have comparable structure, combustion reactivity and primary tar composition. Biomass HTC samples generate chars with similar combustion reactivity and secondary tar composition of coal. Abstract: Hydrothermal carbonization (HTC) is a thermochemical conversion process in aqueous phase that is well suited for the valorization of waste biomass. The carbonaceous solid phase produced by the HTC process (the so-called hydrochar) shows interesting properties that make it similar to conventional solid fuels. Thus, it may be used in existing coal-handling infrastructures, rendering it particularly attractive for co-firing. Two different biomasses are investigated: walnut shells as biomass richer in lignin, and miscanthus as biomass richer in hemicellulose/cellulose. The properties of the resulting hydrochars are analyzed and compared with those of untreated biomass and of coals typically used in industrial boilers. The HTC treatment results in the reduction of the cellulose/hemicellulose contribution and O/C ratio, and in an increase of aromatic structures, heating value and grindability. The behavior of the hydrochars upon pyrolysis under fast heating conditions typical of pulverized fuel boilers is investigated using a heated strip reactor (HSR). The combustion reactivity tests in a thermogravimetric apparatus show that the HTC treatment levels off the differences between various biomasses, while the HSR treatment generates chars with the same combustion reactivity as char obtained from coal erasing the differences between HTC-derived biomass and fossil fuels. As for char reactivity, the HTC process reduces the impact of the different biomass compositions on tar formation, but few differences are still observed regarding the volatile phase between biomass hydrochar and coal samples. Results are analyzed and discussed with the goal of evaluating the potential of HTC of lignocellulosic biomass to generate green fuels suitable for industrial boilers.